Significance of rescue hybrid endoscopic submucosal dissection in difficult colorectal cases - Hayato Yamaguchi; Masakatsu Fukuzawa; Takashi Kawai; Takahiro Muramatsu; Taisuke Matsumoto; Kumiko Uchida; Yohei Koyama; Akira Madarame; Takashi Morise; Shin Kono; Sakiko Naito; Naoyoshi Nagata; et al. (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Hybrid endoscopic submucosal dissection (ESD), in which an incision is made around a lesion and snaring is performed after submucosal dissection, has some advantages in colorectal surgery, including shorter procedure time and preventing perforation. However, its value for rescue resection in difficult colorectal ESD cases remains unclear. This study evaluated the utility of rescue hybrid ESD (RH-ESD). Methods We divided 364 colorectal ESD procedures into the conventional ESD group (C-ESD, n=260), scheduled hybrid ESD group (SH-ESD, n=69), and RH-ESD group (n=35) and compared their clinical outcomes. Results Resection time was significantly shorter in the following order: RH-ESD (149 [90-197] minutes) >C-ESD (90 [60-140] minutes) >SH-ESD (52 [29-80] minutes). The en bloc resection rate increased significantly in the following order: RH-ESD (48.6%), SH-ESD (78.3%), and C-ESD (97.7%). An analysis of factors related to piecemeal resection of RH-ESD revealed that the submucosal dissection rate was significantly lower in the piecemeal resection group (25% [20%-30%]) than in the en bloc resection group (40% [20%-60%]). Conclusions RH-ESD was ineffective in terms of curative resection because of the low en bloc resection rate, but was useful for avoiding surgery.